Sosialisasi Pemanfaatan Sistem Informasi Akuntansi Berbasis Digital Pada UMKM - Syafrul Antoni; M Karim; Nelly Patria (CV. Multi Kreasi Media, 2024)
The Accounting Information System is a tool for Micro, Small and Medium Enterprises that is very necessary for preparing various efficient and valid reports. Socialization and training on digital-based accounting information systems is carried out with the aim of making MSME actors understand the importance of accounting information systems, so that business actors are expected to be able to use accounting information systems, especially digital, in carrying out their business so that valid information is produced in the decision-making process. This outreach and training was carried out for MSME actors in Kerinci district and Sungaifull city, Jambi province. This service was carried out for MSME actors, namely at Luxio Studio and Queen Laundry. The methods used in this community service are socialization, training and assistance in the use of accounting information systems using digitalization with tutorials and discussions. This service activity can change the perception of MSME actors regarding the importance of accounting information systems, and also MSME actors have the ability to implement digital-based accounting information systems in conducting business.